2019
DOI: 10.1038/s41467-019-12013-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo epigenetic editing of Sema6a promoter reverses transcallosal dysconnectivity caused by C11orf46/Arl14ep risk gene

Abstract: Many neuropsychiatric risk genes contribute to epigenetic regulation but little is known about specific chromatin-associated mechanisms governing the formation of neuronal connectivity. Here we show that transcallosal connectivity is critically dependent on C11orf46, a nuclear protein encoded in the chromosome 11p13 WAGR risk locus. C11orf46 haploinsufficiency was associated with hypoplasia of the corpus callosum. C11orf46 knockdown disrupted transcallosal projections and was rescued by wild type C11orf46 but … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…During the axonal crossover, a multitude of axon guidance factors are required, and defects in the expression of those factors can also cause callosal projection deficits. A recent study described that chromatin remodelling of the axon guidance cue Sema6a caused the callosal defects observed in WAGR Syndrome (OMIM# 194072), a complex disorder including aniridia, kidney tumours, genital abnormalities, and ID [324]. Specifically, this study identified a novel protein, C11orf46/ADP ribosylation factor like GTPase 14 effector protein (ARL14EP), of which mutations were previously associated with ID [325].…”
Section: Epigenetic Modulation In Callosal Projection Neuron Developmentmentioning
confidence: 82%
See 1 more Smart Citation
“…During the axonal crossover, a multitude of axon guidance factors are required, and defects in the expression of those factors can also cause callosal projection deficits. A recent study described that chromatin remodelling of the axon guidance cue Sema6a caused the callosal defects observed in WAGR Syndrome (OMIM# 194072), a complex disorder including aniridia, kidney tumours, genital abnormalities, and ID [324]. Specifically, this study identified a novel protein, C11orf46/ADP ribosylation factor like GTPase 14 effector protein (ARL14EP), of which mutations were previously associated with ID [325].…”
Section: Epigenetic Modulation In Callosal Projection Neuron Developmentmentioning
confidence: 82%
“…Specifically, this study identified a novel protein, C11orf46/ADP ribosylation factor like GTPase 14 effector protein (ARL14EP), of which mutations were previously associated with ID [325]. C11orf46 is a member of the SETDB1-KRAB associated protein (KAP1)-MCAF1 chromatin repressor complex, and controls H3K9 methylation levels at the Sema6a promoter, cell-autonomously in projection neurons [324]. The callosal projection phenotype could be rescued by targeted H3K9 re-methylation at the Sema6a locus, indicating a direct epigenetic repressive control over axon guidance receptors in callosal-projecting neurons.…”
Section: Epigenetic Modulation In Callosal Projection Neuron Developmentmentioning
confidence: 99%
“…The risk allele for SCZ led to more frequent skipping of the exon, supporting expression of a novel isoform (Figure 4G and 4H). ARL14EP gene has been shown to play a role in axonal development in the mouse neurons 51 . Here, we propose a novel transcript of this gene with expression in progenitors as a risk factor for SCZ.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a recent study linked the haploinsufficiency of the brain‐specific TF C11orf46 to callosal hypoplasia, leading to a mental retardation syndrome. [ 142 ] Remarkably, the authors used that same TF as a dCas9 fusion effector to rescue the neurodevelopmental disorder, showing that deciphering the molecular mechanisms of brain disorders can be crucial for therapeutic development.…”
Section: Therapeutic Promise Of Epigenetic Editingmentioning
confidence: 99%